Alteration of prognostic efficacy of albumin‐bilirubin grade and Child‐Pugh score according to liver fibrosis in hepatocellular carcinoma patients with Child‐Pugh A following hepatectomy. Issue 1 (19th September 2021) - Miyata, Tatsunori; Yamashita, Yo‐ichi; Arima, Kota; Higashi, Takaaki; Hayashi, Hiromitsu; Imai, Katsunori; Nitta, Hidetoshi; Chikamoto, Akira; Beppu, Toru; Baba, Hideo
Abstract: Background: The albumin‐bilirubin (ALBI) grade was developed to predict the prognosis of patients with hepatocellular carcinoma (HCC), which can stratify the prognosis even in HCC patients with Child‐Pugh A. We evaluated the prognostic efficacy of the ALBI grade and Child‐Pugh classification in HCC patients with Child‐Pugh A stratified by the presence or absence of advanced fibrosis or a preoperative biomarker for advanced fibrosis. Methods: We retrospectively analyzed 490 consecutive HCC patients with Child‐Pugh A who underwent initial hepatectomies. The accuracy of prognostic prediction using both models was compared by the presence or absence of advanced fibrosis (F3‐4) and its predictor, the preoperative platelet count (PLT). Results: The prognostic accuracy of the ALBI grade was better in patients without advanced fibrosis (F3‐4; likelihood ratio: 4.39, corrected Akaike information criterion [AICc]: 453.0, P  = .074), but Child‐Pugh score was better in the advanced fibrosis group (likelihood ratio: 10.67, AICc: 915.2, P  = .0014). In the high PLT group (≥140 × 10 3 /μL), the prognostic accuracy using the ALBI grade was better in overall survival (OS) and relapse‐free survival (RFS), but in the low PLT group, the Child‐Pugh score was the more accurate model in OS and RFS. Conclusions: Depending on the degree of fibrosis or preoperative PLT, the ALBI grade and Child‐Pugh score may provide more accurate prognoses after initial hepatectomy in HCC patients with Child‐Pugh A. Abstract : Depending on the degree of fibrosis and preoperative platelet count (PLT), the albumin‐bilirubin (ALBI) grade or Child‐Pugh score may provide more accurate prognoses after initial hepatectomy in HCC patients with Child‐Pugh A.